The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1097/ccm.0b013e31817d7f5c
|View full text |Cite
|
Sign up to set email alerts
|

A new severe acute necrotizing pancreatitis model induced by l-ornithine in rats

Abstract: We have developed a simple, noninvasive model of acute necrotizing pancreatitis in rats by intraperitoneal injection of 3 g/kg L-ornithine. Interestingly, we found that, compared with L-arginine, L-ornithine was even more effective at inducing pancreatitis. Large doses of L-arginine produce a toxic effect on the pancreas, at least in part, through L-ornithine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
56
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 30 publications
8
56
0
3
Order By: Relevance
“…Basic amino acids, at doses of a few grams per kilogram body weight, trigger AP in rodents (8,23,46,53). Recently, it was suggested that L-arginine, which is most often used in these animal models of AP, may act through another basic amino acid L-ornithine (53).…”
Section: Characterizing Ros Responses Induced By L-ornithinementioning
confidence: 99%
“…Basic amino acids, at doses of a few grams per kilogram body weight, trigger AP in rodents (8,23,46,53). Recently, it was suggested that L-arginine, which is most often used in these animal models of AP, may act through another basic amino acid L-ornithine (53).…”
Section: Characterizing Ros Responses Induced By L-ornithinementioning
confidence: 99%
“…7 This finding suggested a major role for arginase (rather than NOS) in the catabolism of L-arginine. In the present study, we have shown that pretreatment Arginase is a key enzyme of the hepatic urea cycle, so it was not surprising that the highest enzyme activity was found in the liver of rats.…”
Section: Discussionmentioning
confidence: 84%
“…Most of the IP injected L-arginine is converted to Lornithine rather than L-citrulline, 7,8 therefore indicating a major role of arginase in the catabolism of this basic amino acid. Furthermore, we have recently shown that administration of Lornithine induces a more severe pancreatitis compared with Larginine.…”
mentioning
confidence: 99%
See 2 more Smart Citations